A study on the figure drawing of local historical comics / Mohamad Akmal Ariff Kamarudin - Kamarudin, Mohamad Akmal Ariff (2015)
The purpose ofthis research is to study on the figure drawing of local historical comics. The human figure is a wonderful structure, made to order for cartoonists. Once the cartoonists have a good command of the basic figure, they can draw cartoon characters in any pose they can imagine. Comic are a global sensation these days. The comic book has been a source of amusement and entertainment for children and adults alike since the 19th century. Some of these cartoon stories are rr.eant to be very hwnorous, but the term "comic book" often brings to mind images of colourful and courageous superheroes, along with equally as ghastly super villains. Comic books are magazines that are comprised of several comic strips